Pengembangan Bahan Ajar Kimia Materi Larutan Asam dan Basa Berbasis Chemo Edutainment Untuk Siswa SMK TI Kelas XI - Chairiah Chairiah; Albinus Silalahi; Wesly Hutabarat (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. This research aims to know the feasibility of Chemistry Materials  for grade eleventh SMK in the second semester for acids and bases solution topic that exist today in accordance with BSNP (National Education Standards Beureu); to know the feasibility of Chemistry Materials  based chemo edutainment for students  grade eleventh SMK in the second semester for acids and bases solution topic in accordance with BSNP (National Education Standards); to know the differences of increase learning outcomes that learned with Chemistry Materials based chemo edutainment for acids and bases solution topic compared than learning outcomes that learned with Chemistry Materials without the development; and to know the differences of increase students motivation learning outcomes that learned with Chemistry Materials  based chemo edutainment for acids and bases solution topic compared than students motivation learning outcomes that learned with Chemistry Materials  without the development. This type of research was development using a model ADDIE (Analysis, Design, Development, Implementation and Evaluations). The population in this research was  all of students  grade eleventh SMK. The sample in this research was SMK Negeri 1 Stabat much as two classes and have  totaling students is 64 . The results showed that: (1) the chemistry materials  publisher X and Y for acids and bases solution topic in accordance with BSNP (National Education Standards) is quite feasible, but there are some that need to be developed; (2) Chemistry materials  that developed for acids and bases solution topic has a decent based on the feasibility of standardizing the contents is  4.11, Language feasibility is 4.24, Presentation feasibility is 4,16 Graphically feasibility is 4,42; (3) there are significant differences in student learning outcomes with the implementation of the chemistry materials  based chemo edutainment was better than the learning outcomes of students with Chemistry materials  without the development (Sig <α and tcount> t table) is 0.00 <0.05 and 4.013> 1.694; (4) the increase of students motivation learning outcomes with the implementation of the chemistry materials based chemo edutainment was higher (77,92) than the students motivation learning outcomes with Chemistry materials  without the development (63,78).Keyword: chemistry teaching materials, solution of acids and bases, chemo edutainment, learning outcomes, motivation to learn